Pharmacometrics Markup Language (PharmML): Opening New Perspectives for Model Exchange in Drug Development. (15th June 2015) - Swat, MJ; Moodie, S; Wimalaratne, SM; Kristensen, NR; Lavielle, M; Mari, A; Magni, P; Smith, MK; Bizzotto, R; Pasotti, L; Mezzalana, E; Comets, E; et al.
<x xml:space="preserve">Abstract</x> The lack of a common exchange format for mathematical models in pharmacometrics has been a long‐standing problem. Such a format has the potential to increase productivity and analysis quality, simplify the handling of complex workflows, ensure reproducibility of research, and facilitate the reuse of existing model resources. Pharmacometrics Markup Language (PharmML), currently under development by the Drug Disease Model Resources (DDMoRe) consortium, is intended to become an exchange standard in pharmacometrics by providing means to encode models, trial designs, and modeling steps.